A novel function for vimentin: the potential biomarker for predicting melanoma hematogenous metastasis - Li Man; Zhang Baogang; Sun Baocun; Wang Xuan; Ban Xinchao; Sun Tao; Liu Zhiyong; Zhao Xiulan (Journal of Experimental & Clinical Cancer Research, 2010)
Abstract Background The incidence of malignant melanoma (MM) was occurring at a faster rate than for most neoplasm worldwide, and melanoma metastasis is still the most formidable problem. So it is necessarily to find some biomarkers associated with melanoma metastasis. Methods In our study, 8 spontaneous lung metastatic mice models were created by B16F10 subcutaneously transplantation. The differential protein profiles of two kinds of subcutaneous transplanted tumor tissues, which was parental B16F10 (B16 group) and corresponding lung metastases (B16M group) were detected by two-dimensional differential in-gel electrophoresis (2D-DIGE) combined with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS). Western blotting was used to validate the results, and the clinical significance of individual protein was detected furtherly in a set of human samples. Result In this study, thirty proteins were found to be differentially expressed (ratio > 2 or < -2, P < 0.01) and thirteen of them were identified by MS. Highly expressed proteins in B16M group included cytoskeleton/structure proteins (vimentin, gamma-actin, β-actin, laminin binding protein), the chaperone family of proteins (heavy-chain binding protein, Bip), immunoproteasome assembly (proteasome activator REG alpha) and others involved in glycolysis activity (PGK1, enolase, TPI, human skeletal muscle GAPDH) and protein transport (myoglobin). Vimentin was significantly up-regulated in B16M group compared with B16 group which was validated by western blotting. Immunohistochemistry was performed in a set of clinical samples, the results showed that over-expression of vimentin was frequently observed in primary melanoma patients with hematogenous metastasis (P < 0.05), not associated with lymph node metastasis (P > 0.05). The presence of TNM stage was a independent indicator of poor prognosis for melanoma patients (P = 0.004). Conclusion The aberrant immunohistochemical expression of vimentin in primary melanoma tissues may help to call attention for patients with high risk of hematogenous metastasis. That might be as a novel metastatic indicator for melanoma. In a word, vimentin is not only the dignostic marker but also the hematogenous metastasis predictor for melanomas clinically.